Para quem e como se escreve no campo do currículo? Notas para discussão - Antonio Flavio Moreira Barbosa (Universidade do Minho, 2001)
It is suggested that the task of curriculum theorizing is not only to analyse and challenge current projects and practice, but also to define and evaluate the nature and scope of possible alternatives. To accomplish this task, curriculum specialists need to dialogue with those who participate in the processes of curriculum development. Drawing on these assumptions, works of representative curriculum authors are examined, in order to verify with whom they intend to dialogue and how they write. Difficulties involved in this process are discussed.